Professores iniciantes na docência universitária: problematizações sobre os conhecimentos pedagógicos nos cursos de graduação em Educação Física - Nascimento, Sylvia Fernanda (2023)
The university teaching is a field that considers the conceptions of education that aim at the human qualification associated with the professional education, and it has been discussing teaching practice in the university teaching from the pillars of a university pedagogy, of the teaching knowledge and the professional development. As we coherently think that teaching is a complex action that justifies the deepening of specific pedagogical knowledge to teach, we consider that a professor in the beginning of their teaching activity has the challenge of building their teaching action taking into account the pedagogical dimensions that involve the teaching and learning process in the university teaching. In the Physical Education (PE) area, there are studies that discuss university teaching, but lack investigation about them, mainly referring to topics that promote reflections on the university teaching practice. In this scenario, the question that guides our investigation concentrates on the professor in the beginning of their teaching career in the Physical Education undergraduate course and their relationship with the teaching in the university education. Thus our aim is to understand how the professor in he beginning of teaching activity mobilizes pedagogical knowledge in their teaching action in the Physical Education undergraduate course considering the position that teaching has in their work in the university teaching. Such investigation was supported by methodological procedures that have allowed us to consider the area of university teaching through qualitative research in a perspective of interpretative investigation of the Physical Education professor to focus on their work in this teaching level. Field work occurred through narrative interviews that took place in two phases: in the first one, aiming at creating a bond and knowing the origin of the professor according to their life history; and the second one, in a closer dialogue through the narrative interview with seven guiding points that have outlined the lines. Twelve (12) professors participated in the study of the Physical Education undergraduate course that worked in the university person-to-person teaching, either in the graduation or in the bachelor’s degree course, in private and public institutions of university teaching in the cities that comprise the metropolitan area of Grande Vitória, in the state of Espírito Santo. This group was made of full time professors in the beginning of their teaching careers, that belonged to the university or were paid with an hourly work regime. The narratives of the beginner professors in the teaching practice in the university teaching allowed us to realize that the teaching action of each one of them was built through interaction and sharing knowledge created by experiences of knowledge that were being acquired by their teaching experiences, specific knowledge of their jobs, practical knowledge originated from several sources and varied life contexts. Teaching in the university requires specific pedagogical knowledge that together with some more knowledge will contribute to deepen the understanding of teaching as a complex activity, since it requires a broad view of professional education because it involves human education, comprising not only the pedagogical aspects of teaching, but also the cultural, social and ethical ones.